2018
DOI: 10.1007/s11845-018-1885-z
|View full text |Cite
|
Sign up to set email alerts
|

Disturbing and distressing: a mixed methods study on the psychological impact of end of life care on junior doctors

Abstract: Junior doctors are regularly carrying out tasks related to end of life care, resulting in high levels of psychological distress. Further training and a change in culture are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…There were a further 10 studies including literature reviews, commentaries, and editorials (Table 1). Study participants included final‐year medical students, 6‐25 junior doctors early in their first postgraduate year, 3,13,14,16‐19,26‐42 junior doctors late in internship (>6 months) or in postgraduate year 2 or above 2,14,16,22,24,35,38,42‐57 (Table 1). Twenty‐one studies incorporated feedback or reports from clinical supervisors or training managers 5,7,13,14,17‐19,22,25,31,35,36,39,43,45,55,58‐61 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were a further 10 studies including literature reviews, commentaries, and editorials (Table 1). Study participants included final‐year medical students, 6‐25 junior doctors early in their first postgraduate year, 3,13,14,16‐19,26‐42 junior doctors late in internship (>6 months) or in postgraduate year 2 or above 2,14,16,22,24,35,38,42‐57 (Table 1). Twenty‐one studies incorporated feedback or reports from clinical supervisors or training managers 5,7,13,14,17‐19,22,25,31,35,36,39,43,45,55,58‐61 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…There were a further 10 studies including literature reviews, commentaries, and editorials (Table 1). Study participants included final-year medical T A B L E 1 Study design and participants in papers included in the review of literature 1998 -2019 Dyar 12 McKenzie 2017 15 Minha 16 Morrow 17 Rothwell 18 Scicluna 19 Stroben 21 Wijnen-Meijer 2015 23 Daly 25 Illing 2013 14 Illing Lightmann Tran 24 Watmough 22 Early internship Abuhusain 26 Bennett 27 Bleakley 28 Cave 29 Heidemann 31 Minha 16 Morrow 17 Prozesky 42 Scicluna 19 Watmough 22 Winn 40 Eley 2 Illing 2013 14 Lundin 32 Monrouxe 2018 35 Muthaura 36 Sturman 3 Walker 39 Gome 30 Illing Kelly 37 Linane 38 McKenzie 41 Miles 33 Minter 34 Rothwell 18 Late or post internship Barr 53 Dean 55 Duns 52 Eley 62 Goldacre 2010 50 Goldacre 2014 57 Hill 56 Kassim 49…”
Section: Descriptive Summarymentioning
confidence: 99%
“…This study also revealed that junior physicians have difficulties regarding “discussion of end-of-life care” and “death pronouncement.” Previous qualitative research indicates that “discussion about end-of-life care” and “death pronouncement,” added as domains in this study, are competencies required for residents and are factors related to posttraumatic stress. 36 The “discussion about end-of-life care” includes delivering bad news that the prognosis is limited and there is no curative treatment, which is challenging for junior physicians. 37 , 38 Death pronouncement also involves both knowledge and technical issues (e.g., how to confirm death), as well as communication before and after death (e.g., how to tell the family that the patient has died, how to understand the family's feelings, and how to offer comfort and encouragement).…”
Section: Discussionmentioning
confidence: 99%
“…Peer support within the multi-disciplinary team has been found helpful (Buschbach et al., 2020; Etkind et al., 2017 and it has been found that emotional support and encouraging reflexivity that involves professionals from different disciplines is very helpful (Manning-Jones et al., 2016). This is also important as studies have found that a negative first experience of EoL care can be particularly damaging to a professional’s development (Linane et al., 2019) and that there is a vital importance for members of the EoL care team be supportive of one another (Chan et al., 2016; Harrison et al., 2017). Our study also reinforces the case for the value for facilitated reflective practice that allows professionals to reflect on stressful situations positively.…”
Section: Discussionmentioning
confidence: 99%